A LATP material and its preparation method and use
By using liquid phosphoric acid solution and sintering additives, the problems of high cost, high pollution and low performance in the synthesis of existing LATP solid electrolytes are solved, and high performance and low cost LATP material preparation is achieved, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202411419994.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing LATP solid electrolyte synthesis methods have problems such as high cost, high environmental pollution, low performance and poor consistency. Especially when using ammonium dihydrogen phosphate as the phosphorus source, it will lead to ammonia gas generation, uneven dispersion of solid phase powder and miscellaneous dispersion and miscellaneousness. Phase generation affects ionic conductivity and product consistency.
Use liquid phosphoric acid solution as the phosphorus source, mix it with lithium source, aluminum source, titanium source and sintering aid to perform wet sintering to avoid ammonia generation and segregation, improve reaction uniformity and contact, and use sintering aid to maintain solid liquid Coexisting states to facilitate adequate response.
It reduces production costs, improves the ionic conductivity and consistency of LATP materials, reduces pollution, and the resulting materials are softer and easier to process, suitable for large-scale production.
Smart Images

Figure CN118954467B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion batteries and relates to a solid electrolyte material, in particular to a LATP material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have been widely used in vehicle power, energy storage grid and 3C consumer power fields due to their advantages such as high operating voltage, high energy density and high cycle life. In order to further meet the market demand for lithium-ion batteries, the development of lithium-ion batteries with higher energy density, higher safety and higher cycle life has become an imperative path. The use of solid electrolytes to completely or partially replace liquid electrolytes to form semi-solid / quasi-solid / all-solid batteries has been proven to be an effective means and has gradually become a research and development direction.
[0003] Solid electrolyte is a key factor affecting the performance of solid-state batteries. Among the many solid-state electrolytes, LATP (lithium aluminum titanium phosphate or lithium aluminum titanium phosphate) solid electrolyte has the advantages of low cost, good environmental adaptability, high ion conductivity, etc., and has great potential for the development of mature commercial solid-state batteries.
[0004] However, in the traditional industrial production of LATP solid electrolytes, phosphate salts such as ammonium dihydrogen phosphate are usually used as phosphorus sources. For example, CN108428937A discloses a method for preparing an oxidized solid electrolyte by dry method and an oxidized solid electrolyte, wherein the method comprises mixing metal oxides, hydroxides, carbonates, phosphates or ammonium salts for dry mixing to obtain a solid phase mixture, which is then obtained by solid phase sintering. The scheme using ammonium dihydrogen phosphate as a phosphorus source has the following problems: (1) The raw materials are all solid phase powders, which makes it difficult to evenly disperse ammonium dihydrogen phosphate between the raw material powders; (2) ammonium dihydrogen phosphate will produce ammonia during the reaction, which makes it difficult for the solid phase powders to be in close contact with each other. On the one hand, it is not conducive to the contact inside the solid electrolyte of Shencheng, and on the other hand, it is easy to cause the generation of impurities and the retention of a large number of pores, thereby causing a decrease in ionic conductivity and consistency; (3) The generation of ammonia means a decrease in atomic utilization, and recovery and post-processing are required, which increases production costs and environmental impact. In addition to this solution, in the prior art, there are solutions in which phosphate is mixed with other raw materials to obtain a solution or a low-viscosity slurry with a small solid content, and then spray-dried to obtain a precursor, which is then sintered. On the one hand, these solutions are prone to rust and damage to equipment due to excessively high moisture content. On the other hand, various phosphate raw materials result in costs that are much higher than using common oxide materials. At the same time, due to the different solubilities of various metal ions, serious segregation is often caused, which in turn leads to the formation of impurities and the deterioration of the ionic conductivity of LATP.
[0005] In summary, the existing methods for synthesizing LATP solid electrolytes are not only costly and environmentally harmful, but also not conducive to large-scale industrial production, and the resulting products have low performance and poor consistency. Therefore, it is urgent to propose a new method to synthesize high-performance LATP solid electrolytes quickly, efficiently, and at low cost. Summary of the invention
[0006] In view of the problems existing in the prior art, the object of the present invention is to provide a LATP material and a preparation method and use thereof, wherein the preparation method comprises mixing a lithium source, an aluminum source, a titanium source, a phosphoric acid solution and a sintering aid to obtain a wet material, and sintering the wet material to obtain the LATP material. The present invention uses a liquid phosphoric acid solution as a phosphorus source, which can promote a more complete reaction, avoid the generation of ammonia, improve the atomic utilization rate, reduce pollution and reduce costs, and is suitable for large-scale production; and the obtained LATP material has improved ionic conductivity and consistency, and is softer and easier to process.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a LATP material, the preparation method comprising:
[0009] A lithium source, an aluminum source, a titanium source, a phosphoric acid solution and a sintering aid are mixed to obtain a wet material, and the wet material is sintered to obtain a LATP material.
[0010] The preparation method of the present invention uses a liquid phosphoric acid solution to replace the solid ammonium dihydrogen phosphate phosphate powder used in the prior art, so that other solid raw materials are mixed with the phosphoric acid solution to form a wet material, and then the wet material is directly sintered, and the sintering process is carried out in a solid-liquid coexistence manner, thereby obtaining the LATP material.
[0011] The present invention mixes phosphoric acid and other solid raw materials to obtain a wet material instead of a pure liquid phase, which is beneficial to avoiding corrosion and damage to equipment by a large amount of liquid acidic phosphoric acid; and the present invention directly sinters the wet material without drying and baking, which also effectively avoids the precipitation process between different products of the reaction between phosphoric acid and metal salts and the segregation caused by the drying and baking process.
[0012] In order to realize the sintering process in which the solid phase and the liquid phase coexist in a "wet material", the present invention adds a sintering aid as a solid phase raw material. When the sintering aid is not used, during the sintering process, the temperature rises, phosphoric acid gradually reacts with the metal ions, the generated water is evaporated, and the entire system gradually changes from a wet material state to a solid phase. After the sintering aid is added, as the temperature rises, the sintering aid gradually melts into a liquid, so that the entire system always maintains a solid-liquid mixed state in the high temperature section, thereby ensuring a more complete reaction, better contact, and further ensuring the improvement of the ionic conductivity and consistency of the product.
[0013] As can be seen from the above, the preparation method of the present invention has the following advantages: (1) Liquid phosphoric acid is used as an anion source, and the fluidity of the liquid is used to improve the dispersion uniformity and contact with other solid raw materials, making the reaction more uniform and sufficient; (2) Phosphoric acid does not produce ammonia during the reaction, which makes the contact between the solid raw material powders closer, and also effectively reduces the probability of the formation of impurities, improves the ionic conductivity, and improves the uniformity and consistency of the LATP material; (3) There is no release of ammonia, and the only by-product is water, which effectively improves the atomic utilization rate, reduces pollution, reduces the cost of treating ammonia, and is more suitable for large-scale production; (4) The obtained LATP material not only has better electrochemical properties, but also because there is no pore retention caused by the release of ammonia, the product has a higher degree of density, better uniformity and consistency, and is softer and easier to process.
[0014] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0015] As a preferred technical solution of the present invention, the preparation method includes first mixing the lithium source, aluminum source, titanium source and sintering aid to obtain a dry material, and then mixing the dry material with the phosphoric acid solution to obtain a wet material.
[0016] As a preferred technical solution of the present invention, the molar ratio of Li, Al, Ti and P is (1+x):x:(2-x):3, 0.3≤x≤0.5, and the amount of lithium source, aluminum source, titanium source and phosphoric acid solution is controlled. For example, x can be 0.3, 0.32, 0.34, 0.36, 0.38, 0.4, 0.42, 0.44, 0.46, 0.48 or 0.5, etc.
[0017] As a preferred technical solution of the present invention, the amount of the lithium source is based on (1+x), with an excess of 1% to 50%, for example, 1%, 3%, 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, 38%, 40%, 43%, 45%, 48% or 50%.
[0018] In the present invention, the lithium source volatilizes during the sintering process to cause lithium loss, so the lithium source is controlled to be appropriately excessive.
[0019] As a preferred technical solution of the present invention, the amount of the sintering aid is controlled according to 0.1% to 50% of the total mass of the lithium source, aluminum source and titanium source, for example, 0.1%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, 38%, 40%, 43%, 45%, 48% or 50%, etc.
[0020] As a preferred technical solution of the present invention, the sintering aid includes at least one of boron oxide or metaborate, preferably boron oxide and / or metaborate, and more preferably boron oxide, and the melting point of the sintering aid is lower than the sintering temperature.
[0021] Preferably, the boron oxide comprises B2O3.
[0022] Preferably, the metaborate comprises LiBO2 and / or Li2B4O7.
[0023] As described above, the sintering aid described in the present invention is used to melt into a liquid to maintain the solid-liquid phase environment of the system during the sintering process. Therefore, the sintering aid is preferably a low melting point aid, and the melting point of the sintering aid is lower than the sintering temperature. The content of the sintering aid should be maintained within an appropriate range. When the content is too low, it is difficult to exert the effect of the sintering aid, resulting in more impure phases in the obtained product, impure physical phases, low performance and other unfavorable effects; and when there are too many sintering aids, the sintering aids that do not contain lithium ions will cover the surface of the LATP material too much, making it difficult for lithium ions to be transmitted, and ultimately causing a decrease in ionic conductivity. At the same time, too much sintering aid will also cause the appearance of sintering aid impurity peaks in the physical phase, and even the sintering aid will react with the synthetic raw materials to generate new impurity phases.
[0024] As a preferred technical solution of the present invention, the lithium source includes at least one of lithium carbonate, lithium hydroxide or lithium oxide.
[0025] As a preferred technical solution of the present invention, the aluminum source includes aluminum oxide and / or aluminum hydroxide.
[0026] As a preferred technical solution of the present invention, the titanium source includes titanium dioxide and / or titanate.
[0027] As a preferred technical solution of the present invention, the particle size of the lithium source, aluminum source, titanium source and sintering aid is 10nm~100μm, for example, 10nm, 20nm, 30nm, 40nm, 50nm, 80nm, 100nm, 200nm, 500nm, 700nm, 850nm, 1μm, 3μm, 5μm, 8μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm or 100μm, preferably 50nm~5μm, and more preferably 50nm~2μm.
[0028] As a preferred technical solution of the present invention, the mass percentage concentration of the phosphoric acid solution is 75% to 98%, for example, 75%, 78%, 80%, 83%, 85%, 88%, 90%, 93%, 95% or 98%, etc., preferably 83% to 88%, and more preferably 85%.
[0029] As a preferred technical solution of the present invention, the sintering process includes primary calcination, primary crushing, secondary calcination and secondary crushing.
[0030] In the present invention, the first calcination is to induce grain formation, and the second calcination is to allow grain growth. If a two-stage sintering is directly performed, the sintering process is not controlled and easy to cause the formation of impurities, resulting in low performance. Therefore, two-stage sintering is used in the synthesis process of the present invention, and it is meaningless to add two crushings after only one calcination.
[0031] In the present invention, after the first calcination, the material is preferably crushed once for re-crushing, which not only reduces the particle size and is beneficial to controlling the particle size, but also increases the contact between the materials, further ensuring the reduction of the generation of impurities, that is, the crushing and reorganization after the first sintering avoids the agglomeration of the sintered material and the generation of impurities; subsequently, through the second calcination and the second crushing, a nanometer-scale powder material is obtained, and the tedious processes of drying, baking and graded grinding are omitted; therefore, it is meaningless to only carry out one calcination and then crush twice to the target particle size, and the effect of the specific sintering and crushing process of the present invention cannot be achieved.
[0032] Preferably, the heating rate of the primary calcination is 3-7°C / min, for example, 3°C / min, 4°C / min, 5°C / min, 6°C / min or 7°C / min, the temperature is 600-800°C, for example, 600°C, 620°C, 640°C, 660°C, 680°C, 690°C, 700°C, 710°C, 720°C, 740°C, 760°C, 780°C or 800°C, preferably 690°C-720°C, and the time is 3-5h, for example, 3h, 3.3h, 3.5h, 3.8h, 4h, 4.3h, 4.5h, 4.8h or 5h, etc.
[0033] Preferably, the particle size of the primary crushing is 0.1-50 μm, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 23 μm, 25 μm, 28 μm, 30 μm, 33 μm, 35 μm, 38 μm, 40 μm, 43 μm, 45 μm or 50 μm, etc., preferably 0.2-10 μm, and more preferably 0.2-2 μm.
[0034] Preferably, the heating rate of the secondary calcination is 1-5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, the temperature is 800-1000°C, for example, 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, 920°C, 940°C, 960°C, 980°C or 1000°C, and the time is 3-5h, for example, 3h, 3.3h, 3.5h, 3.8h, 4h, 4.3h, 4.5h, 4.8h or 5h, etc.
[0035] Preferably, the particle size of the secondary crushing is less than 1 μm, for example 900nm, 800nm, 700nm, 600nm, 500nm, 400nm, 300nm, 200nm, 100nm, 80nm, 60nm, 40nm, 20nm, 10nm, 8nm, 5nm, 3nm or 1nm, etc., preferably 50~500nm.
[0036] In the present invention, if the temperature of the first calcination is too low, it is easy to cause the formation of impurities, while the heating rate has no obvious effect. If the temperature of the second calcination is too high or too low, it will lead to adverse effects such as low crystallinity, impurity formation, and poor performance; and if the heating rate is too fast or too slow, it is related to the particle size of the crystal. If the heating rate is too fast, the grains are small and the consistency is poor, but if the heating rate is too slow, the grains in some areas will be too large. The heating rate needs to be selected in an appropriate range, usually 1~5℃ / min.
[0037] In the present invention, the temperature of the secondary calcination is preferably higher than that of the primary calcination. The primary calcination plays a role in crystal phase synthesis, and the secondary calcination plays a role in grain growth. The state of grain growth depends on the secondary calcination, and the calcination temperature is higher than that of the primary calcination.
[0038] In the present invention, the final product LATP material after secondary crushing has multiple application directions, and the most suitable particle size is determined according to the application direction. Generally, there are suitable application directions between 50nm and 500nm.
[0039] The present invention does not specifically limit the specific equipment used for the mixing and crushing, and the equipment can be selected according to actual conditions and needs.
[0040] Exemplarily, the mixing equipment includes at least one of an agate mortar, a small juicer, an important mixer, a ball mill, a V-type mixer or a high mixer.
[0041] Exemplarily, the equipment for the primary crushing and the secondary crushing includes at least one of a flat air flow mill, a fluidized bed air flow mill, a circulating air flow mill, an impact crusher, an expansion crusher, a ball mill, a high-speed rotating projectile mill, a high-speed rotating impact mill, a sand mill or a roller mill.
[0042] In a second aspect, the present invention provides a LATP material, wherein the LATP material is obtained according to the preparation method described in the first aspect, and the chemical formula of the obtained LATP material includes Li 1+x Al x Ti 2-x (PO4)3, 0.3≤x≤0.5, for example, x can be 0.3, 0.32, 0.34, 0.36, 0.38, 0.4, 0.42, 0.44, 0.46, 0.48 or 0.5, etc.
[0043] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery contains the LATP material described in the second aspect as a solid electrolyte.
[0044] It should be noted that due to space limitations and to avoid redundancy, the present invention does not list all point values in the above numerical range one by one, but is not limited to the listed numerical values, and other unlisted numerical values in the corresponding numerical range are also applicable.
[0045] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0046] The preparation method of the present invention uses liquid phosphoric acid as an anion source, and improves the dispersion uniformity and contact with other solid raw materials by virtue of the fluidity of the liquid, so that the reaction is more uniform and sufficient; phosphoric acid does not generate ammonia during the reaction, so that the contact between the solid raw material powders is closer, and the probability of the generation of the impurity phase is effectively reduced, the ion conductivity is improved, and the uniformity and consistency of the LATP material are improved; and the only by-product is water, so the atomic utilization rate is effectively improved, and the pollution is reduced, and the cost increased by the treatment of ammonia is reduced, and it is more suitable for large-scale production; the LATP material obtained by the preparation method of the present invention not only has better electrochemical performance as a solid electrolyte, but also has higher density, better uniformity and consistency, and is softer and easier to process because there is no pore retention caused by the release of ammonia. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 , Figure 3 and Figure 5 They are respectively the XRD patterns of the LATP materials obtained in Example 1, Example 4 and Comparative Example 1;
[0048] Figure 2 , Figure 4 and Figure 6 The EIS test spectra of the LATP materials obtained in Example 1, Example 4 and Comparative Example 1 are respectively. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0050] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.
[0051] Example 1
[0052] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), the preparation method comprising:
[0053] 2560g lithium carbonate (25% excess), 660g alumina, 5755g titanium dioxide, and 450g boron oxide B2O3 (accounting for 5% of the total mass of lithium carbonate, alumina and titanium dioxide) with a particle size of 10nm~100μm were weighed and mixed at high speed in a high-speed mixer for 2h to obtain dry material, which was transferred to a sagger, and 14700g concentrated phosphoric acid with a mass concentration of 85% was added thereto to obtain wet material, which was loaded into a sintering furnace for sintering. The sintering procedure included heating to 700℃ at 5℃ / min and keeping warm for 4 hours, taking out the sample for primary crushing, heating to 900℃ at 3℃ / min and keeping warm for 4 hours, taking out the sample for secondary crushing to obtain LATP material.
[0054] Example 2
[0055] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 A method for preparing (PO4)3) is disclosed, wherein the amounts of the raw materials are changed to 256 g lithium carbonate (25% excess), 66 g alumina, 575.5 g titanium dioxide, 45 g boron oxide B2O3 (accounting for 5% of the total mass of lithium carbonate, alumina and titanium dioxide) and 1470 g concentrated phosphoric acid with a mass concentration of 85%. Except for the above, the other conditions are exactly the same as those in Example 1.
[0056] Example 3
[0057] This embodiment provides a LATP material (Li 1.4 Al 0.4 Ti 1.6 A method for preparing (PO4)3) is disclosed, wherein the amounts of the raw materials are changed to 275 g lithium carbonate (25% excess), 87 g alumina, 542.6 g titanium dioxide, 46 g boron oxide B2O3 (accounting for 5% of the total mass of lithium carbonate, alumina and titanium dioxide) and 1470 g concentrated phosphoric acid with a mass concentration of 85%. Except for the above, the other conditions are exactly the same as those in Example 1.
[0058] Example 4
[0059] This embodiment provides a LATP material (Li 1.5 Al 0.5 Ti 1.5 A method for preparing (PO4)3) is disclosed, wherein the amounts of the raw materials are changed to 295 g lithium carbonate (25% excess), 109 g alumina, 508.1 g titanium dioxide, 46 g boron oxide B2O3 (5% of the total mass of lithium carbonate, alumina and titanium dioxide) and 1470 g concentrated phosphoric acid with a mass concentration of 85%. Except for the above, the other conditions are exactly the same as those in Example 1.
[0060] Example 5
[0061] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), wherein the amount of lithium carbonate used is adjusted from 256 g lithium carbonate (25% excess) to 207 g lithium carbonate (1% excess). Except for the above, other conditions are exactly the same as those in Example 2.
[0062] Example 6
[0063] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), wherein the amount of lithium carbonate used is adjusted from 256 g lithium carbonate (25% excess) to 226 g lithium carbonate (10% excess). Except for the above, other conditions are exactly the same as those in Example 2.
[0064] Example 7
[0065] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7(PO4)3), wherein the amount of lithium carbonate used is adjusted from 256 g lithium carbonate (25% excess) to 277 g lithium carbonate (35% excess). Except for the above, other conditions are exactly the same as those in Example 2.
[0066] Example 8
[0067] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), wherein the amount of lithium carbonate used is adjusted from 256 g lithium carbonate (25% excess) to 308 g lithium carbonate (50% excess). Except for the above, other conditions are exactly the same as those in Example 2.
[0068] Example 9
[0069] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 A preparation method for (PO4)3) is disclosed, wherein the amount of boron oxide B2O3 is adjusted from 45 g (5% of the total mass of lithium carbonate, alumina and titanium dioxide) to 5 g (0.56% of the total mass of lithium carbonate, alumina and titanium dioxide). Except for the above, other conditions are exactly the same as those in Example 2.
[0070] Example 10
[0071] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 A preparation method for (PO4)3) is disclosed, wherein the amount of boron oxide B2O3 is adjusted from 45 g (5% of the total mass of lithium carbonate, alumina and titanium dioxide) to 15 g (1.67% of the total mass of lithium carbonate, alumina and titanium dioxide). Except for the above, other conditions are exactly the same as those in Example 2.
[0072] Embodiment 11
[0073] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 A preparation method for (PO4)3), wherein the amount of boron oxide B2O3 is adjusted from 45 g (5% of the total mass of lithium carbonate, alumina and titanium dioxide) to 90 g (10% of the total mass of lithium carbonate, alumina and titanium dioxide). Except for the above, other conditions are exactly the same as those in Example 2.
[0074] Example 12
[0075] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 The preparation method of Example 2 is as follows: the amount of boron oxide B2O3 is adjusted from 45g (5% of the total mass of lithium carbonate, aluminum oxide and titanium dioxide) to 230g (25.6% of the total mass of lithium carbonate, aluminum oxide and titanium dioxide). Except for the above, other conditions are exactly the same as those in Example 2.
[0076] Example 13
[0077] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), wherein 1470 g of concentrated phosphoric acid having a mass concentration of 85% is adjusted to 4165 g of concentrated phosphoric acid having a mass concentration of 30%, while keeping the molar amount of phosphoric acid unchanged. Except for the above, other conditions are exactly the same as those in Example 2.
[0078] Embodiment 14
[0079] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), wherein 1470 g of concentrated phosphoric acid having a mass concentration of 85% is adjusted to 2499 g of concentrated phosphoric acid having a mass concentration of 50%, while keeping the molar amount of phosphoric acid unchanged. Except for the above, other conditions are exactly the same as those in Example 2.
[0080] Embodiment 15
[0081] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), wherein 1470 g of concentrated phosphoric acid having a mass concentration of 85% is adjusted to 1666 g of concentrated phosphoric acid having a mass concentration of 75%, while keeping the molar amount of phosphoric acid unchanged. Except for the above, other conditions are exactly the same as those in Example 2.
[0082] Example 16
[0083] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3) is a preparation method, wherein after the first calcination, a second calcination is performed directly without a first crushing, and then a second crushing is performed. Except for the above, other conditions are exactly the same as those in Example 2.
[0084] Embodiment 17
[0085] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3) is a preparation method, wherein after the first calcination, no first crushing is performed, and a second calcination is performed directly, followed by a first crushing and a second crushing. Except for the above, other conditions are exactly the same as those in Example 2.
[0086] Embodiment 18
[0087] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3) is a preparation method, wherein the preparation method performs a primary calcination followed by a primary crushing and a secondary crushing, and omits the secondary calcination. Except for the above, other conditions are exactly the same as those in Example 2.
[0088] Embodiment 19
[0089] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 The preparation method of (PO4)3) comprises the following steps: first calcination is performed, and then first crushing and second crushing are performed directly. The temperature of the first calcination is adjusted from 700°C to 900°C, and the time is adjusted from 4h to 8h. The second calcination is omitted. Except for the above, other conditions are exactly the same as those in Example 2.
[0090] Embodiment 20
[0091] This embodiment provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), wherein the preparation method uses an equal mass of metaborate LiBO2 to replace boron oxide B2O3. Except for the above, other conditions are exactly the same as those in Example 2.
[0092] Comparative Example 1
[0093] This comparative example provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), wherein the preparation method uses ammonium dihydrogen phosphate powder as a phosphorus source, and the preparation method comprises:
[0094] Weigh 951g lithium carbonate, 275.5g alumina, 2444.9g titanium dioxide, and 6210g ammonium dihydrogen phosphate powder with a particle size of 25μm. Place the ammonium dihydrogen phosphate powder in a high-speed mixer and mix at a speed of 400rpm for 5min. Then add all the remaining materials at 100rpm, mix at 800rpm for 5min, and then mix at 1200rpm for 5min. Take out the mixed precursor and put it in a box furnace for sintering. Sintering includes a process of staged heating and staged constant temperature. The specific procedure is: room temperature to 700℃, 5℃ / min, and keep warm for 2 hours. Take out the oxide solid electrolyte precursor, crush it, and continue to put it in a bowl to obtain a solid electrolyte precursor in close contact. The program temperature is raised to 900℃ at 5℃ / min and kept warm for 2 hours. Take out the sintered product and perform air flow crushing to obtain LATP material.
[0095] Comparative Example 2
[0096] This comparative example provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3) is a preparation method, wherein 1467 g of ammonium dihydrogen phosphate powder with a particle size of 25 μm is prepared into an aqueous solution, and the aqueous solution is used to replace phosphoric acid. Except for the above, other conditions are exactly the same as those in Example 2.
[0097] Comparative Example 3
[0098] This comparative example provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), wherein the preparation method does not use sintering aids such as boron oxide B2O3. Except for the above, other conditions are exactly the same as those in Example 2.
[0099] Comparative Example 4
[0100] This comparative example provides a LATP material (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), wherein the preparation method comprises drying the obtained wet material before sintering to obtain a solid mixture, and using the solid mixture for sintering. Except for the above, other conditions are exactly the same as those in Example 2.
[0101] Characterization and Testing:
[0102] Ⅰ. Physical phase test: Figure 1 , Figure 3 and Figure 5They are the XRD patterns of the LATP materials obtained in Example 1, Example 4 and Comparative Example 1. It can be seen from the figures that the obtained LATP materials all correspond to the phase corresponding to PDF:35-0754.
[0103] Ⅱ. Ionic conductivity test: Ionic conductivity is used to describe the ease of lithium ion transfer in solid electrolytes and is expressed by σ (unit: S / cm). During the test, the LATP material powder is die-cast into an electrolyte sheet at a certain pressure, and then the electrolyte sheet is sintered into a dense ceramic sheet. After gold spraying or brushing conductive silver paste on both sides, an EIS test is performed using an electrochemical workstation to obtain its resistance value R, which is then calculated according to the formula σ=L / (R×S), where L is the thickness of the electrolyte sheet during the test (cm), and S is the area of the electrolyte sheet during the test (cm 2 );
[0104] Figure 2 , Figure 4 and Figure 6 The three curves in the figure are the EIS test spectra of the LATP materials obtained in Example 1, Example 4 and Comparative Example 1. The three curves in the figure are three measurements of the same batch of samples at different positions, and the average ionic conductivity is calculated. By comparison, it can be seen that the preparation method of the present invention is more suitable for synthesizing Li 1.3 Al 0.3 Ti 1.7 (PO4)3 type LATP, and when the lithium content increases, the purity of the material decreases and the ionic conductivity also decreases.
[0105] Other results are recorded in Table 1.
[0106] Table 1
[0107] Group Average particle size of LATP after secondary crushing (nm) Average ionic conductivity (S / cm) Finished product status Example 1 90 <![CDATA[6.1*10 -4 ]]> White, powder Example 2 100 <![CDATA[5.8*10 -4 ]]> White, powder Example 3 95 <![CDATA[4.5*10 -4 ]]> White, powder Example 4 90 <![CDATA[2.8*10 -4 ]]> White, powder Example 5 96 <![CDATA[4.5*10 -4 ]]> White, powder Example 6 97 <![CDATA[3.5*10 -4 ]]> White, powder Example 7 90 <![CDATA[4.2*10 -4 ]]> White, powder Example 8 95 <![CDATA[3.0*10 -4 ]]> White, powder Example 9 96 <![CDATA[4.3*10 -4 ]]> White, powder Example 10 105 <![CDATA[3.8*10 -4 ]]> White, powder Embodiment 11 102 <![CDATA[3.7*10 -4 ]]> White, powder Example 12 101 <![CDATA[2.8*10 -4 ]]> White, powder Example 13 100 <![CDATA[4.7*10 -4 ]]> White, powder Embodiment 14 100 <![CDATA[5.0*10 -4 ]]> White, powder Embodiment 15 107 <![CDATA[5.3*10 -4 ]]> White, powder Example 16 110 <![CDATA[2.2*10 -4 ]]> White, powder Embodiment 17 90 <![CDATA[2.5*10 -4 ]]> White, powder Embodiment 18 100 <![CDATA[2.0*10 -4 ]]> White, powder Embodiment 19 110 <![CDATA[2.6*10 -4 ]]> White, powder Embodiment 20 104 <![CDATA[5.5*10 -4 ]]> White, powder Comparative Example 1 110 <![CDATA[1.9*10 -4 ]]> White, blocky Comparative Example 2 93 <![CDATA[4.5*10 -6 ]]> White, flake Comparative Example 3 100 <![CDATA[0.9*10 -4 ]]> White, blocky Comparative Example 4 109 <![CDATA[3.0*10 -4 ]]> White, blocky
[0108] It can be seen from Table 1 that:
[0109] Compared with the comparative example, the LATP material with phosphoric acid as the phosphorus source generally has higher ionic conductivity after being crushed into nanomaterials in the embodiments of this case, and the material after sintering is generally white powder, which is easy to crush, has the advantages of high performance and easy processing, and has a wide range of application prospects. It can be seen from Examples 1-20 that in the synthesis process of LATP materials, it is necessary to optimize the lithium content, the excess degree of lithium source, the type and content of sintering aids, the state of wet materials (such as by changing the phosphate concentration and dosage adjustment), and the sintering process to obtain the LATP solid electrolyte with the best performance.
[0110] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0111] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0112] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a LATP material, characterized in that: The preparation method comprises: A lithium source, an aluminum source, a titanium source, a phosphoric acid solution and a sintering aid are mixed, and the molar ratio of Li, Al, Ti and P is (1+x):x:(2-x):3, 0.3≤x≤0.
5. The amount of the lithium source, the aluminum source, the titanium source and the phosphoric acid solution is controlled, and the mass percentage concentration of the phosphoric acid solution is 75%~98% to obtain a wet material, and the wet material is sintered to obtain a LATP material.
2. The method for preparing the LATP material according to claim 1, characterized in that: The preparation method comprises: firstly mixing the lithium source, the aluminum source, the titanium source and the sintering aid to obtain a dry material, and then mixing the dry material with the phosphoric acid solution to obtain a wet material.
3. The method for preparing the LATP material according to claim 1, characterized in that: The amount of the lithium source is based on (1+x) and is in excess of 1% to 50%.
4. The method for preparing the LATP material according to claim 1 or 2, characterized in that: The amount of the sintering aid is controlled according to 0.1% to 50% of the total mass of the lithium source, the aluminum source and the titanium source.
5. The method for preparing the LATP material according to claim 1 or 2, characterized in that: The sintering aid includes at least one of boron oxide or metaborate; the boron oxide includes B2O3; the metaborate includes LiBO2 and / or Li2B4O7; the melting point of the sintering aid is lower than the sintering temperature.
6. The method for preparing the LATP material according to claim 1 or 2, characterized in that: The lithium source includes at least one of lithium carbonate, lithium hydroxide or lithium oxide; the aluminum source includes aluminum oxide and / or aluminum hydroxide; the titanium source includes titanium dioxide and / or titanate; the particle size of the lithium source, aluminum source, titanium source and sintering aid is 10nm~100μm.
7. The method for preparing the LATP material according to claim 1 or 2, characterized in that: The sintering process includes primary calcination, primary crushing, secondary calcination and secondary crushing; the heating rate of the primary calcination is 3-7°C / min, the temperature is 600-800°C, and the time is 3-5h; the particle size of the primary crushing is 0.1-50μm; the heating rate of the secondary calcination is 1-5°C / min, the temperature is 800-1000°C, and the time is 3-5h; the particle size of the secondary crushing is <1μm.
8. A LATP material, characterized in that: The preparation method according to any one of claims 1 to 7, wherein the chemical formula of the obtained LATP material includes Li 1+x Al x Ti 2-x (PO4)3, 0.3≤x≤0.
5.
9. A lithium ion battery, characterized in that: Contains the LATP material according to claim 8 as a solid electrolyte.
Citation Information
Patent Citations
Dry preparation method for oxidized solid electrolyte and oxidized solid electrolyte
CN108428937A
Method for efficiently synthesizing pure-phase lithium titanium phosphate electrolyte
CN114725491A
Solid electrolyte lithium titanium aluminum phosphate and preparation method thereof
CN115321509A